KREATIVITAS PESERTA DIDIK PADA SEKOLAH DASAR DI MASA PANDEMI COVID 19 DALAM KONTEKS FENOMENOLOGIS HUSSERLIAN - Putra Afriadi; Mifta Khairina (Universitas Negeri Medan, 2020)
This study aims to discuss the limitations of creativity in the COVID 19 pandemic phenomenon in the view of Edmund Husserl's philosophy. phenomenology only wants to highlight what is visible to consciousness or only wants to see what is visible as far as it is visible, which is called pure phenomena. The method used in this research is qualitative research methods. The approach used in this research is the phenomenological approach. Several techniques are used including interviews, observation and documentation. The subjects of this study were students in elementary schools. In creativity, it is stated that there are four ways to achieve creativity, namely, Person, Product, Process, Press. At the elementary school level, students fall into the little-C category. For example, doing different activities, new everyday things, and returning to aspects of local culture.